Investment opportunity set, corporate governance practices and firm performance - Hutchinson, Marion; Gul, Ferdinand A (Journal of Corporate Finance, 2004)
Prior research on the relationship between corporate controls and firm performance is premised on the notion that, in theory, there is direct association between corporate governance and firm performance. However, extensive research has produced mixed and often weak results. In this paper, we posit, as a primary relationship, a negative association between growth and firm performance and then examine whether corporate governance variables moderate this negative relationship. Our results support this notion and show that the role of corporate governance variables in firm performance should be evaluated in the context of the firm's external environment measured in this study in terms of growth opportunities.